Insight into molecular compositions of soluble species from sequential thermal dissolution of Liuhuanggou bituminous coal and its extraction residue. (1st October 2019) - Xu, Mei-Ling; Wei, Xian-Yong; Yu, Xin-Yue; Liu, Fang-Jing; Wu, Qi-Cong; Li, Sheng; Wang, Sheng-Kang; Liu, Guang-Hui; Liu, Zhong-Qiu; Guo, Xian-Hou; Zhang, Yang-Yang; Zong, Zhi-Min
Highlights: Normal alkanes and arenes are the most abundant in SPI and SP1, respectively. Both SP2 and SPII are rich in arenes. Alkyl-substituted benzenes in SPI and SPII are higher than those in SP1 and SP2 . Abundant heteroatom-containing species are concentrated into SP3 and SPIII . N 1 and N 1 O 1 species are predominant in SPIII and SP3, respectively. Abstract: Liuhuanggou bituminous coal (LBC) and its extraction residue (ER) were thermally dissolved sequentially in cyclohexane, toluene, and ethanol at 300 °C to obtain soluble portions (SPs) 1–3 (SP1 -SP3 ) from the thermal dissolution (TD) In the total yield (TY) of 10.4% and SPs I-III (SPI -SPIII ) from the TD in the TY of 4.9%, respectively. The SPs were analyzed by multiple analytical tools, including gas chromatograph/mass spectrometer (GC/MS), quadrupole exactive orbitrap mass spectrometer (QEOTMS), and Fourier transform infrared spectrometer. The analysis with GC/MS shows that normal alkanes are the most abundant in SPI, while arenes are predominant in SP1, SP2, and SPII . According to the analysis with QEOTMS, abundant heteroatom-containing organic species were concentrated into SP3 and SPIII with molecular masses of 150–750 u . The relative contents of N 1 and N 1 O 1 species are predominantly high in SPIII and SP3, respectively.